Critical analysis of research on the impact of visual literacy for learning: strengths, weaknesses and recommendations for improvement. Issue 3 (3rd July 2019) - Guo, Daibao; Zimmer, Wendi; Matthews, Sharon D.; McTigue, Erin M.
Abstract: Situated on the overlap between visual literacy and content area literacy, we conducted a systematic literature review regarding the impact of visuals for learning in K-12 content area classrooms. The purpose was to critically analyse the methodological rigor of this research base and provide direction for future research. Additionally, we provide a pragmatic update to a methodological quality screening tool and apply it for visual literacy research. In this manuscript, we present the detailed coding procedure and data analysis: We screened 1693 articles that yielded an initial corpus of 88 articles which were evaluated with methodological quality indicators. This process yielded a final set of 44 articles. Finally, we synthesized the methodological weakness and highlight exemplars of methodological strengths as models for future research. Finally, we conclude with additional recommendations for rigorous future research.